2017
DOI: 10.1002/app.44873
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation and antifouling analyses of cellulose acetate/nanodiamond nanocomposite membranes in water treatment

Abstract: In this study, nanocomposite membranes based on cellulose acetate (CA) and nanodiamond (ND) were prepared by applying phase inversion methods. In order to achieve efficient dispersion and more hydrophilic NDs, they were functionalized via heat treatment (ND-COOH). The prepared nanocomposite membranes were characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), contact angle, porosity measurement, tensile strength, and abrasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 80 publications
(91 reference statements)
3
30
0
Order By: Relevance
“…Etemadi et al prepared pristine and carboxylated ND‐embedded cellulose acetate (CA) membranes. Obtained results revealed that the presence of both pristine and carboxylated NDs improved thermal, mechanical, and antibacterial characteristics of the membrane, and also, CA/ND‐COOH membrane showed even better properties than CA/ND membrane owing to the better dispersion of carboxylated NDs.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…Etemadi et al prepared pristine and carboxylated ND‐embedded cellulose acetate (CA) membranes. Obtained results revealed that the presence of both pristine and carboxylated NDs improved thermal, mechanical, and antibacterial characteristics of the membrane, and also, CA/ND‐COOH membrane showed even better properties than CA/ND membrane owing to the better dispersion of carboxylated NDs.…”
Section: Introductionsupporting
confidence: 91%
“…It can be seen that the hydrophilicity of the membranes improved with increasing the content of ND‐COOH and ND‐PEG nanoparticles. This improvement in the membrane hydrophilicity can be ascribed to the presence of hydrophilic functional groups on the surface of modified ND nanoparticles . Moreover, PE/ND‐PEG nanocomposite membranes have minimum contact angle values as a result of hydrophilic hydroxyl groups of PEG chains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As reported in the literature, nanocomposite membranes such as HDPE/SiO 2 [11], polyethersulfone (PES)/ Stöber silica [30], CA/organically modified montmorillonite [7], polyamide (PA)/multi-wall carbon nanotube (MWCNT) [31], polysulfone/GO-TiO 2 [9], and PVDF/TiO 2 [32] enhanced the performance of polymeric membranes in HA removal from contaminated water. In our previous work, pristine and carboxylated ND particles, i.e., ND and ND-COOH were added to the CA polymer to investigate the anti-fouling properties of the prepared nanocomposite CA membranes in HA removal from contaminated water [33]. Obtained results were promising; however, anti-fouling properties were far from our preliminary goal.…”
Section: Introductionmentioning
confidence: 99%